The Effect of Estradiol on Renal Function in Reversible and Irreversible Unilateral Ureteral Obstruction in Rats - Zahra Lak; Akbar Vahdati; Mehdi Nematbakhsh (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: The ureteral obstruction (UO) is the most common clinical disorders. This study was designed to investigate the renoprotective effect of estradiol in unilateral UO (UUO) and reversible UUO (RUUO).METHODS: Eighty-four ovareictomized Wistar rats were assigned into 14 groups. Group 1 was sham operated group. All the groups 2-14 were subject to UUO, however they received additional treatments. Group 2-4 received test substances (vehicle, 0.1 or 0.05 mg/kg of estradiol) and sacrificed after 3 days. Group 5-7 received test substances and after 3 days followed by RUUO (obstruction removal) and after one day post RUUO were sacrificed. Group 8-9 followed by RUUO after 3 days and simultaneously received estradiol and after one day post RUUO were sacrificed. Group 10-12 followed by RUUO after 3 days and simultaneously received test substances and after 3 days post RUUO were sacrificed. Group 13-14 received test substances followed by RUUO and received test substances again and after 3 days post RUUO were sacrificed.RESULTS: The estradiol reduced body weight significantly (p<0.05) in UUO, and the uterus weight (UW) increased significantly by estradiol (p<0.05). The increased serum levels of blood urea nitrogen (BUN) and creatinine (Cr), and kidney weight (KW) induced by UUO (p<0.05) were not attenuated by estradiol. Estradiol treatment did not alter the levels of BUN, Cr, KW, Cr clearance (CrCl), urine sodium excretion and urine flow when compared with control.CONCLUSION: Although the protective role of estradiol in cardiovascular system is well accepted, however our findings suggest that its protection during UUO or after RUUO in renal system cannot be certain.KEYWORDS: estradiol, ureteral obstruction, renal function, rat